Sustainable Rice Straw Management 2019
DOI: 10.1007/978-3-030-32373-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Rice-Straw Mushroom Production

Abstract: The rice-straw mushroom (Volvariella volvacea) has a distinct flavor, pleasant taste, and rich protein content. It has low production costs and a cropping duration of approximately 45 days-making it an effective means for poverty alleviation for those farmers who grow it. Farmers in Vietnam, the Philippines, and Cambodia grow it. Rice straw is one of the most common substrates used for growing this mushroom. The mushroom can grow well in both outdoor and indoor conditions; however, outdoor cultivation has risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
12
0
3
Order By: Relevance
“…According to the interviews, these sales could generate an income for the agripreneurs. This is in line with the studies by Jegadeesh, et al [27] and Thuc, et al [28] who found that the use of SMS could increase farmers' income and the economic status of the rural population [30][31][32]. The study found that even though 87.5 percent (35 people) knew that SMS could be reused for the next mushroom cultivation, yet none of the agripreneurs practiced it.…”
Section: Agripreneurs' Level Of Readiness For Environmentally-friendly Mushroom Cultivation Waste Managementsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the interviews, these sales could generate an income for the agripreneurs. This is in line with the studies by Jegadeesh, et al [27] and Thuc, et al [28] who found that the use of SMS could increase farmers' income and the economic status of the rural population [30][31][32]. The study found that even though 87.5 percent (35 people) knew that SMS could be reused for the next mushroom cultivation, yet none of the agripreneurs practiced it.…”
Section: Agripreneurs' Level Of Readiness For Environmentally-friendly Mushroom Cultivation Waste Managementsupporting
confidence: 89%
“…As these crops use only agricultural waste as a medium of growth, limited use of space and low technology use, this provides the opportunity for rural people to grow the small-scale industry and farm at the local level [27]. This expansion will generate side income and reduce poverty among farmers [28]. This has opened up job opportunities from home, in addition to small and medium enterprises to the surrounding population, especially women and young people [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, the interventions from the perspective of circular bioeconomy involve recirculation of material flows and adoption of restoration cycle (formation of new biomass). The interventions in crop residue management are conservation agriculture (Shyamsundar et al, 2019), in-situ straw incorporation (Chivenge et al, 2019), biomass energy production (Jiang et al, 2012;Hiloidhari et al, 2014;Ngan et al, 2019), biofuel generation (Liska et al, 2014;Prasad et al, 2020), crop residue-based biorefinery (Cherubini andUlgiati, 2010), biochar production (Joseph et al, 2013;Singh and Sidhu, 2014;Windeatt et al, 2014;Singh et al, 2015;Zhou et al, 2018;Li et al, 2019), composting (Aynehband et al, 2017;Nghi et al, 2019) and mushroom production (Philippoussis, 2009;NPMCR, 2014;Lohan et al, 2018;Thuc et al, 2019).…”
Section: Recommended Interventions In Crop Residue Managementmentioning
confidence: 99%
“…Several diseases could develop when Pb enters and contaminates the food chain. Pb can also be found in straw mushroom fruit bodies that grow on Pb-contaminated rice straw and stubble, where the highest Pb concentration is recorded in egg and the mature stage of straw mushroom (V. volvacea) [126]. The chances of these metals in straw mushrooms entering the consumer food chain are high since the button to egg stages are the preferred harvesting stages for straw mushrooms [127].…”
Section: Translocation Of Heavy Metal Contamination In Mushroom Food ...mentioning
confidence: 99%